Congruency of scent and lighting as a driver of in-store evaluations and behavior. - Koh, Su Huay. (2009)
While previous studies have extensively examined the individual effects of environmental stimuli on the store environment and store evaluation, few researches have studied the interaction effects between environmental stimuli. In this report, we extend the notion of Gestalt psychology to consumers’ perceptions of retail environment and demonstrate that consumers evaluate store environment holistically. Specifically, in accordance to the Optimal Arousal Theory, the arousing dimension of environmental stimuli is one dimension along which holistic evaluations occur. With that, this report aims to examine the interaction effects between two environmental stimuli, namely ambient scent and lighting, along the arousal dimension on evaluations of the store environment, store merchandise, store experience and approach/ avoidance behaviors.